POLA KOMUNIKASI GURU DAN ORANG TUA DALAM MENIGKATKAN MOTIVASI BELAJAR SISWA - Suraji (Al-mujahidah, 2020)
The purpose of this study is to determine the Communication Patterns of Teachers and Parents of Students in Increasing Student Motivation at SD Negeri 5 Banyu Biru, Semarang Regency, Central Java. The method used is descriptive quantitative method. Based on the description of the communication patterns between teachers and parents at SD Negeri 5 Banyu Biru, it can be concluded that the communication patterns used by teachers and parents at SD Negeri 5 Banyu Biru are: a) interpersonal communication because this communication is carried out by two people or more and the message delivered can also be replied directly; b) group communication because communication that occurs in a group can make existing information easily known by other student guardians. There are some Factors supporting and hindering teacher to communicate with parents at SD Negeri 5 Banyu Biru, those are: (1) Guardians who are proactive with their constructive ideas, criticisms and suggestions are one of the supporting factors for communication at SD Negeri 5 Banyu Biru, (2) limited activity in School so that it has a positive effect on smooth communication, especially between teachers and guardians of students, (3) The use of media and technology is not optimal because there are no special teachers to handle or operate school websites. (4) Limited facilities and infrastructure owned by the school.